1992
DOI: 10.3177/jnsv.38.471
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Safflower Phospholipid and Soybean Phospholipid on Plasma and Liver Lipids in Rats Fed a Hypercholesterolemic Diet.

Abstract: SummaryThe effect of dietary safflower phospholipid (Saf-PL) and soybean phospholipid (Soy-PL) on plasma, liver, and fecal lipids in rats fed a hypercholesterolemic diet was compared with that of triglyceride mixture (controls). Triglyceride mixture (SP-Oil) of safflower oil and palm oil (8:2) contained almost comparable amounts of linoleic acid to safflower phospholipid or soybean phospholipid. Concentration of total cholesterol in plasma of rats fed the Saf PL and Soy-PL diets were significantly decreased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…Conceivably, therefore, phospholipids originating from other origins may be equally effective in decreasing hepatic fatty acid synthesis . The observation that both phospholipids originating from soybean and egg yolk and those originating from mold (6) and safflower seed (7)(8)(9) are also effective in decreasing serum lipid levels in the rat support this possibility, but confirmation remains to be sustained. Polyunsaturated fatty acids decrease the activity and gene expression of enzymes in hepatic fatty acid synthesis more than saturated and monounsaturated fatty acids (10)(11)(12)(13)(14)(15).…”
Section: Dietarymentioning
confidence: 66%
“…Conceivably, therefore, phospholipids originating from other origins may be equally effective in decreasing hepatic fatty acid synthesis . The observation that both phospholipids originating from soybean and egg yolk and those originating from mold (6) and safflower seed (7)(8)(9) are also effective in decreasing serum lipid levels in the rat support this possibility, but confirmation remains to be sustained. Polyunsaturated fatty acids decrease the activity and gene expression of enzymes in hepatic fatty acid synthesis more than saturated and monounsaturated fatty acids (10)(11)(12)(13)(14)(15).…”
Section: Dietarymentioning
confidence: 66%
“…Studies on the detailed lipid composition of fish roe have shown that, in general, they contain large amounts of eicosapentaenoic acid (20:5n-3), docosahexaenoic acid (22:6n-3, DHA), phospholipids (PL), and cholesterol Kaitaranta, 1980;Tocher and Sargent, 1984;Bledsoe et al, 2003). PLs are effective in lowering plasma lipids (Brook et al, 1986;Iwata et al, 1992) and the majority of 22:6 in fish roe lipids is associated with PL; it is a characteristic of fish roe lipids that differs from fish oil. We have previously reported that intake of lipids extracted from salted herring roe products reduces plasma lipid and glucose concentrations in mice .…”
Section: Introductionmentioning
confidence: 99%
“…By a previous experiment, we showed that safflower phospholipid (Saf-PL) suppressed the elevation of plasma and liver cholesterol in rats fed a hypercholesterolemic diet [l0]. We also demonstrated that safflower phospholipid had the advantage of increasing of the level of HDL cholesterol, reducing liver cholesterol, and increasing the excretion of fecal neutral steroids more than soybean phospholipid (Soy-PL) in rats fed such a diet [ 11 ] . However, investigations of whether safflower phospholipid reduces the concentrations of plasma and liver cholesterol in rats fed a cholesterol-free diet have not been carried out.…”
Section: Discussionmentioning
confidence: 99%